Reconsidering the Role of Neuronal Intrinsic Properties and Neuromodulation in Vestibular Homeostasis - Beraneck, Mathieu; Idoux, Erwin (Frontiers in Neurology, 2012)
The sensorimotor transformations performed by central vestibular neurons constantly adapt as the animal faces conflicting sensory information or sustains injuries. To ensure the homeostasis of vestibular-related functions, neural changes could in part rely on the regulation of 2° VN intrinsic properties. Here we review evidence that demonstrates modulation and plasticity of central vestibular neurons’ intrinsic properties. We first present the partition of Rodents’ vestibular neurons into distinct subtypes, namely type A and type B. Then, we focus on the respective properties of each type, their putative roles in vestibular functions, fast control by neuromodulators and persistent modifications following a lesion. The intrinsic properties of central vestibular neurons can be swiftly modulated by a wealth of neuromodulators to adapt rapidly to temporary changes of ecophysiological surroundings. To illustrate how intrinsic excitability can be rapidly modified in physiological conditions and therefore be therapeutic targets, we present the modulation of vestibular reflexes in relation to the variations of the neuromodulatory inputs during the sleep/wake cycle. On the other hand, intrinsic properties can also be slowly, yet permanently, modified in response to major perturbations, e.g., after unilateral labyrinthectomy (UL). We revisit the experimental evidence, which demonstrates that drastic alterations of the central vestibular neurons’ intrinsic properties occur following UL, with a slow time course, more on par with the compensation of dynamic deficits than static ones. Data are interpreted in the framework of distributed processes that progress from global, large-scale coping mechanisms (e.g., changes in behavioral strategies) to local, small-scale ones (e.g., changes in intrinsic properties). Within this framework, the compensation of dynamic deficits improves over time as deeper modifications are engraved within the finer parts of the vestibular-related networks. Finally, we offer perspectives and working hypotheses to pave the way for future research aimed at understanding the modulation and plasticity of central vestibular neurons’ intrinsic properties.